Deslocamento de peixes migradores no rio Uruguai e no sistema misto de migração da barragem de Itaipu. - Hahn, Lisiane (2007)
Many Neotropical fish species displace extensive migration in order to complete their life cycles, since the needed habitats for reproduction, growing and feeding are many times distant by hundreds kilometers. The application of new tools and technologies to monitor and investigate the movements, to determinate the areas used by species and on the evaluation of fish passages are an alternative to answer the questions related to behavior patterns in short term, optimizing not just the results but also the resources applied in these studies. In this thesis, the movements of six long distance migratory species in high flow waters and fish ways were evaluated. In the first part were described the movements of 73 individuals of Salminus brasiliensis (Cuvier, 1816) in 400 km in the upper Uruguay River, between November 2001 and April 2004, using radiotelemetry techniques. In the second part, the efficiency of Migration Channel located at ITAIPU on fish migration was investigated. Were radiotagged and tracked 77 individuals of six species between October 2004 and March 2006. The experiences and results obtained in these researches provided important indicatives about the radiotelemetry application in freshwater environments and Neotropical migratory fish species, about the migratory behavior of Salminus brasiliensis in free stretches of the Uruguay River and about migratory behavior of fish species on fish passages.